Evaluation of a new short generic measure of health status: howRu - Tim Benson; Steve Sizmur; Justin Whatling; Seref Arikan; Dianna McDonald; David Ingram (Journal of Innovation in Health Informatics, 2010)
Background Quality of life is paramount for patients and clinicians, but existing measures of health were not developed for routine use. Objectives This paper describes the development and testing of a new generic tool for measuring health related quality of life (HRQoL) with direct comparison to the SF-12 Health Survey. Methods The new tool (howRu) has four items (discomfort, distress, disability and dependence), rated using four levels (none, a little, quite a lot and extreme), providing 256 possible states (44); it has an aggregate scoring scheme with a range from 0 (worst) to 12 (best). Psychometric properties were examined in a telephone survey, which also recorded SF-12. Results The howRu script is shorter than SF-12 (45 words vs 294 words) and has better readability statistics. 2751 subjects, all with long-term conditions (average age 62, female 62.8%), completed the survey; 21.7% were at the ceiling (no reported problems on any dimension); 0.9% at the floor. Inter-item correlations, Cronbach's alpha and principal factor analysis suggest that a single summary score is appropriate. Correlations between the physical and mental components of both howRu and SF-12 were as expected. Across all patients the howRu score was correlated with PCS-12 (r=0.74), MCS-12 (r=0.49) and the sum of PCS- 12 and MCS-12 (r=0.81). Subjects were classified by howRu score, primary condition, the number of conditions suffered, age group, duration of illness and area of residence. Across all six classifications, the correlation of themean howRu score with the mean PCS-12 for each class was r=0.91, with MCS-12, r=0.45 and with the sum of PCS-12 and MCS-12, r=0.97. Conclusions howRu is a new short generic measure of HRQoL, with good psychometric properties. It generates similar aggregate results to SF-12. It could provide a quick and easy way for practitioners to monitor the health of patients with long-term conditions.